2017
DOI: 10.1038/pr.2017.170
|View full text |Cite
|
Sign up to set email alerts
|

Term vs. preterm cord blood cells for the prevention of preterm brain injury

Abstract: BACKGROUNDWhite matter brain injury in preterm infants can induce neurodevelopmental deficits. Umbilical cord blood (UCB) cells demonstrate neuroprotective properties, but it is unknown whether cells obtained from preterm cord blood (PCB) vs. term cord blood (TCB) have similar efficacy. This study compared the ability of TCB vs. PCB cells to reduce white matter injury in preterm fetal sheep.METHODSHypoxia-ischemia (HI) was induced in fetal sheep (0.7 gestation) by 25 min umbilical cord occlusion. Allogeneic UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 43 publications
1
28
1
Order By: Relevance
“…Microglial cell activation was decreased across all white matter brain regions examined in FGR+UCBC lambs. The cerebral and systemic anti-inflammatory benefits of UCBC therapy have been reported previously in a preclinical model of preterm brain injury induced via acute hypoxia-ischemia [10]. Li et al also showed a significant correlation between increasing density of activated microglia and loss of oligodendrocytes at 10 days after insult, indicative that neuroinflammation is strongly associated with oligodendrocyte development.…”
Section: Neuroinflammationmentioning
confidence: 59%
See 2 more Smart Citations
“…Microglial cell activation was decreased across all white matter brain regions examined in FGR+UCBC lambs. The cerebral and systemic anti-inflammatory benefits of UCBC therapy have been reported previously in a preclinical model of preterm brain injury induced via acute hypoxia-ischemia [10]. Li et al also showed a significant correlation between increasing density of activated microglia and loss of oligodendrocytes at 10 days after insult, indicative that neuroinflammation is strongly associated with oligodendrocyte development.…”
Section: Neuroinflammationmentioning
confidence: 59%
“…Umbilical cord blood collected at birth has a high cell yield and a wide variety of stem and progenitor cells, which are shown to mediate positive benefits on glial cells, neurons, and cells that maintain the BBB [7,[14][15][16]. These and other studies show that the neuroprotective or neuroreparative benefits of UCBC for the immature brain acts through anti-apoptotic, anti-inflammatory, pro-angiogenic, neurogenic, anti-oxidant, and BBB protective mechanisms [9][10][11][12].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The UCB cells used in this study were from sheep UCB, due to the limited availability of sheep-specific antibodies, we were unable to identify the proportion of various cell types within the UCB samples. However, previous studies have shown UCB cells from autologous and allogeneic sheep to be efficacious in a sheep model of preterm brain injury (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…UCB cells were cryopreserved in dimethyl sulfoxide (10% DMSO, Sigma in FBS) and stored in liquid nitrogen for subsequent administration to lambs. UCB cells were thawed as previously described and have shown that administration of immediately thawed cells is effective at reducing inflammation and cell death (Aridas et al, 2016;Li et al, 2017;Paton et al, 2018;Paton et al, 2019). Briefly, cells were rapidly thawed in a 37 • C water bath with 10 ml media, centrifuged for 5 min at 300 × g and then supernatant was removed and cells resuspended in media and counted using a hemocytometer and trypan blue.…”
Section: Umbilical Cord Blood Cell Preparationmentioning
confidence: 99%